Level of important Factors Affecting Students’ Enrollment Decision at Luang Prabang Teacher Training College - XAIYALATH, Deuan; SALITXAY, Timnoy; SOULIYA, Toulakone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to determine the general background of students and to analyze the factors affecting students’ enrollment decisions at Luang Prabang Teacher Training College. The sample consisted of 290 students who participated through a questionnaire-based survey. The level of influence on enrollment decisions was assessed across seven factors: personal reasons, environmental/institutional quality, financial, curriculum, family, social, and future opportunity factors. Data were analyzed using SPSS version 22. through descriptive statistics, including frequency, percentage, mean, and standard deviation. The demographic analysis revealed that the majority of students were female (50.3%), aged between 31–40 years (74.1%), married (91%), and primarily employed as public primary school teachers (51.7%). Most respondents reported a monthly income ranging from 2,000,001 to 3,500,000 LAK (69.7%) and resided in Luang Prabang Province (51.4%). Overall, the analysis of factors affecting enrollment decisions indicated a high level of importance (X̄ = 4.17). Among the seven factors, personal reason factors showed the highest level of importance (X̄ = 4.54), rated as very high, followed by future opportunity factors (X̄ = 4.30), also rated as very high. The lowest level of importance was found in financial factor (X̄ = 3.78) when compared to other factors. The high rating of personal reason factors suggests that students are primarily motivated by their passion for the teaching profession and their belief that further education will enhance their knowledge, skills, and modern teaching methods.